Analysis of Study Results in Class X Students of SMA Negeri 2, Buru District in the Pandemi Of Covid 19 - Anggalina Kao; Bahmid Hasbullah; Siti Divinubun (Peneliti.net, 2023)
This research was conducted to find out the learning outcomes of PJOK students during the Covid-19 pandemic. Which aims to find out the results of educational reports, the concept of learning outcomes, to find out student learning outcomes using online media. This research is motivated by student learning outcomes including the low category. This is caused by factors of boring learning activities, only one-way learning activities from teacher to student, and lack of student motivation in learning. This study used a qualitative approach with qualitative methods, while the focus of the research being analyzed was to analyze student learning outcomes during the previous Covid-19 pandemic from various schools at SMA Negeri 2 Namlea, Buru Regency. The data collection technique carried out in this study was using research instruments, namely documentation, observation , interview guidelines. The research results that the researchers found related to student learning outcomes through online media showed that student learning outcomes through online media had increased learning outcomes